Preferensi Risiko Memoderasi Pengaruh Sanksi Perpajakan dan Kualitas Pelayanan pada Kepatuhan Wajib Pajak - Puspita, Ni Nyoman Trida; Jati, I Ketut (E-Jurnal Akuntansi; Vol 34 No 7 (2024)DO - 10.24843/EJA.2024.v34.i07.p17, 2024)
This study aims to determine the effect of tax sanctions and service quality on individual taxpayer compliance moderated by the moderating variable. The research location is at the Kantor Pelayanan Pajak Pratama Gianyar. The number of samples is 100 people determined by using purposive sampling method. Data was collected through the questionnaire method. The data analysis technique used is Moderated Regression Analysis. Research shows results include tax sanctions have a positive effect on WPOP compliance, service quality has no effect on WPOP compliance, risk preferences weaken the positive effect of tax sanctions on WPOP compliance, and risk preferences do not moderate the positive effect of service quality on compliance WPOP. Keywords: Tax Sanctions; Service Quality; Risk Preferences; Taxpayer Compliance